Predictive Values of Early Parental Loss and Psychopathological Risk for Physical Problems in Early Adolescents - Tafà, Mimma; Cerniglia, Luca; Cimino, Silvia; Ballarotto, Giulia; Marzilli, Eleonora; Tambelli, Renata (Frontiers in Psychology, 2018)
Background: Several studies have suggested that the early loss of parents is a potentially traumatic experience, exposing adolescents to a higher risk for the onset of psychopathological symptoms. Furthermore, research has shown an association between the loss of a parent in childhood and subsequent physical illnesses, but much less attention has been given to the predictive role of loss in the development of physical illness in adolescence. Methods: From a larger normative sample, we selected 418 early adolescents (and their surviving parents) each of whom had lost a parent in their first three years of life. We evaluate the offspring’s and parents’ psychopathological symptoms, dissociation, and physical problems over a six-year period. Univariate and multivariate Cox proportional hazard regression analyses with time-dependent variables were used to examine the predictive values of the adolescents’ and surviving parents’ psychopathological symptoms, and youths’ demographic characteristics (sex and age) for the occurrence of physical illness during a six-year period of follow-up. Results: Independently of sex, the psychopathological risk of the surviving parents’ and adolescents’ affective problems and dissociation has been found to predict the occurrence of physical illnesses. Furthermore, dissociation was the most significant predictor of significant physical problems. Conclusion: These results may be relevant and an addition to the previous literature, opening up new possibilities for prevention and intervention that are oriented toward greater support for children who have experienced the loss of one parent and for surviving parents.